Retrospective analysis of prostate cancer detection using mpMR/US-fusion and cognitive biopsy - V. S. Petov; A. K. Bazarkin; E. S. Krupinov; A. O. Morozov; M. S. Taratkin; A. F. Abdusalamov; A. V. Amosov; D. V. Enikeev (Вестник урологии)
Introduction. Transrectal biopsy under US-control has been standard diagnostic method for prostate cancer (PCa) detection for over 30 years. However, TRUS-guided biopsy is not without well-known drawbacks. MR-targeted biopsy methods were proposed to eliminate the drawbacks and improve detection rate of clinically significant Pca. Cognitive and mpMR/US-fusion biopsies have become the most widely used MR-targeted biopsies. However, there are contradictory data on detection of clinically significant Pca when comparing mpMR/US-fusion and cognitive biopsies.Objective. To compare the detection rate of clinically significant prostate cancer performing cognitive and mpMR/US-fusion biopsies.Materials and methods. Inclusion criteria: PSA > 2.0 ng/ml and/or a positive DRE, and/or a suspicious lesion on TRUS, and PI-RADSv2.1 score ≥ 3. The outcomes evaluated are the detection of clinically significant Pca (ISUP ≥ 2), the overall PСa detection, the detection of clinically insignificant Pca, histological yield (proportion of positive cores, maximum cancer core length).Results. Retrospective data analysis was performed: cognitive biopsy was performed in 102 patients and mpMR/US-fusion biopsy in 176 patients. The median age was 63 years, prostate volume 46 cc. The median PSA was 6.4 ng/ml in the mpMR/US-fusion and 6.7 ng/ml in the cognitive biopsy group. MpMR/US-fusion and cognitive biopsies were comparable about the detection rate of clinically significant (30.3% vs 25.0%; p=0.329) and overall Pca detection rate (50.5% and 42.1%; p = 0.176). It was detected to be less clinically insignificant Pca in the cognitive biopsy group (11.8% vs. 25.5%; p = 0.007).  The proportion of positive cores (30.5% and 29.5% respectively; p = 0.754) and maximum cancer core length (6.6 mm vs 7.6 mm; p = 0.320) were equal when comparing cognitive and mpMR/US-fusion biopsies. The proportion of positive cores with clinically significant Pca was higher in the cognitive biopsy group (18.6% vs 13.1%; p = 0.029).Conclusion. Both cognitive and mpMR/US-fusion biopsies are equally accurate for clinically significant Pca detection. Therefore, cognitive biopsy may be an alternative to mpMR/US-fusion biopsy in hospitals where mpMR/US-fusion technology is not currently available.